KEMAMPUAN RASIO CAMEL DALAM MEMPREDIKSI PERTUMBUHAN LABA BANK BUMN - Permatasari, Rinny; Saiful, Saiful; Midiastuty, Pratana P (JURNAL FAIRNESS, 2016)
The  focus  of  this  study  aimed  to  analyze  the  influence  of  financial  ratios  to  future earnings growth consist of  CAR, KAP, PPAP, NIM, ROA, ROA, and LDR. The sample in this research is the state-owned banking company listed on the Indonesian Stock Exchange which issued  quarterly  and  annual  financial statements  for  fiscal  year  2009  to 2013,  namely  PT. Bank  Mandiri  (Persero),  Tbk,  PT.  Bank  Rakyat  Indonesia  (Persero),  Tbk,  and  PT.  Bank Negara Indonesia (Persero), Tbk. These three state-owned banks are located in the category of Commercial Bank Business Activities (BUKU) 4 with core capital above Rp. 30 trillion. Data collection methods used are literature and documentation. Data were analyzed using classic  assumption  test,  multiple  linear  regression  analysis  test,  and  test  the  hypothesis  by using the tool SPSS. This study could not provide the empirical evidence on the influence of CAR, KAP, PPAP, NIM, BOPO, ROA, dan LDR to earning growth.